Acceptability of rectal self-sampling in non-clinical venues for chlamydia and gonorrhea testing among men who have sex with men: A cross-sectional study in Shenzhen, China - Weng, Rongxing; Ning, Ning; Zhang, Chunlai; Wen, Lizhang; Ye, Jianbin; Wang, Honglin; Li, Jing; Chen, Xiangsheng; Cai, Yumao (Frontiers in Public Health, 2022)
Background: Rectal chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections among men who have sex with men (MSM) have become an increasingly important concern. The study aimed to explore (1) the acceptability of rectal self-sampling for chlamydia and gonorrhoea testing among MSM in non-clinical venues in Shenzhen city, China; (2) factors associated with the acceptability of rectal self-sampling; and (3) factors associated with rectal CT or NG infections. Methods: This cross-sectional study was conducted in two non-clinical settings in Shenzhen, China, from April 2021 to October 2021. Multivariate logistic regression analysis was performed to explore the factors associated with acceptance of rectal self-collection for CT and NG testing. Results: Of the 306 MSM who were offered to perform rectal self-sampling, 133 (43.5%) accepted and 96.2% (128/133) of them successfully provided valid rectal sample. The prevalence of urogenital CT and NG infections among 303 MSM was 4.29% and 0.66%, respectively. The prevalence of rectal CT and NG infections among 128 participants was 31.25% and 9.38%, respectively. Participants having high school or below education, having been diagnosed as HIV infection, and having CT/NG testing history showed a higher acceptance of rectal self-collection for CT and NG testing. Conclusion: This study reported that rectal self-sampling in non-clinical venues for CT and NG testing among MSM was barely acceptable and feasible in China. Most CT and NG infections would have been missed if urethral screening was offered alone, which implies that the CT screening should be scaled up in the above setting.